The risk of clopidogrel resistance is associated with ABCB1 polymorphisms but not promoter methylation in a Chinese Han population. - Jia Su; Qinglin Yu; Hao Zhu; Xiaojing Li; Hanbin Cui; Weiping Du; Lindan Ji; Maoqing Tong; Yibo Zheng; Hongyu Xu; Jianjiang Zhang; Yunyun Zhu; et al. (PLoS ONE, 2017)
The goal of our study was to investigate the contribution of ABCB1 expression to the risk of clopidogrel resistance (CR). Platelets functions were measured using the Verify-Now P2Y12 assay. Applying Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP), the single-nucleotide polymorphisms (SNPs) was tested. Using bisulphite pyrosequencing assay, we investigated the association of the ABCB1 DNA methylation levels and CR. It was shown that female, hypertension, and lower albumin levels increased the risk of CR (P<0.05). If patients did not have hypoproteinaemia or had hypertension, the SNP in rs1045642 was associated with CR (CC vs. TT: albumin ≥35, P = 0.042; hypertension, P = 0.045; C vs. T: albumin ≥35, P = 0.033; hypertension, P = 0.040). Additionally, the platelet inhibition of the CT+TT genotype in rs1128503 was larger than that of the CC genotype (P = 0.021). Multivariate logistic regression analysis showed that male, higher albumin and hsCRP decreased the risk of CR, and the stent size maybe positively correlated with CR. The SNP in rs1045642 was related to all-cause mortality (P = 0.024). We did not find any relationship between the methylation levels of the ABCB1 promoter and CR. In conclusions, our study indicated that ABCB1 polymorphisms might be useful in further evaluating the pathogenesis of CR.